PERBANDINGAN NILAI-NILAI PENDIDIKAN KARAKTER DALAM SERIAL ANIMASI RIKO THE SERIES SEASON 5 DAN NUSSA SEASON 3 PADA PLATFORM YOUTUBE - Eka, Sanita; Saleh, Muhammad; Saguni, Suarni Syam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and comparison the values of character education in the animated series Riko The Series Season 5 and Nussa Season 3. This research is classified as a descriptive qualitative research type with data sources in the form of the two animated series on the YouTube platform. The data collection techniques used include observation techniques, viewing notes, and documentation. Data analysis techniques are carried out through the stages of data collection, data reduction, data presentation, and conclusion drawn. The results of this study show (1) there are various character education values in the Riko The Series Season 5 animation series, namely religious, honest, tolerant, disciplined, hard work, creative, independent, curiosity, respect for achievements, communicative/friendly, peace-loving, social care, and responsibility. (2) there are several character education values in the Nussa Season 3 animated series, namely religious, honest, disciplined, creative, independent, curious, communicative/friendly, peace-loving, socially caring, and responsibility. (3) There is a comparison of the value of character education in the two animated series. The similarities, both display important values such as religious, honest, disciplined, creative, independent, curious, communicative, peace-loving, social care, and responsibility, with similar educational goals and approaches. The difference lies in the context of application, variations and values highlighted. Riko The Series Season 5 contains more variety including tolerance, hard work, and appreciation for achievements and highlights curiosity, while Nussa Season 3 highlights religious values. The conclusion of the study shows that the two animated series have the potential to be an effective character learning medium.